[Circular letter] Panyam - Wedgwood, C. H. (Adam Matthew Digital, 1928)
Typescript letter telling of the burning down of the CMS station at Mwari by some of the Seyawa people, and the work done on building a new station; preceded by a covering letter from CMS officer E. Hayward in Bath, July 12, 1928, to Rev. Hooper, suggesting that the CMS find some funds to help with the rebuilding work